Hubungan Dukungan Keluarga dengan Perilaku Pencegahan Penularan Tuberkulosis (TBC) di Puskesmas Tilamuta Kabupaten Boalemo Gorontalo - Izzatul Azka Dunggio; Heny Nurmayunita (USADA NUSANTARA : Jurnal Kesehatan Tradisional, 2026)
Tuberculosis (TB) is a contagious disease that remains a major public health problem, especially in developing countries such as Indonesia. One of the important efforts in controlling TB is through preventive behavior to reduce transmission. Family support is considered to play a role in influencing such behavior. This study aimed to determine the relationship between family support and TB transmission prevention behavior at Tilamuta Public Health Center, Boalemo Regency, Gorontalo. This study employed a quantitative analytic design with a cross-sectional approach. The sample consisted of 30 respondents selected using total sampling technique. Data were collected using structured questionnaires and analyzed using the Chi-Square test with a significance level of 0.05. The results showed that most respondents had moderate family support (63.3%) and poor prevention behavior (86.7%). The Chi-Square test result showed a p-value of 0.465 (p > 0.05), indicating that there was no significant relationship between family support and TB transmission prevention behavior. In conclusion, there is no significant relationship between family support and TB prevention behavior. Therefore, other interventions such as health education are needed to improve preventive behavior among patients.